Central Coast Pride participants, one with a poster reading 'Silence is Violence: Resist,' June 2017 (2017)
Image shows participants at the 2017 Central Coast Pride, also known as SLO Pride. The Central Coast Queer Archive and Oral History Project (CCQAP) is using images like these to document LGBTQ history on the central coast.